Cladocera of Malaysia and Singapore with new records, redescriptions, and remarks on some species - Idris, B. A. G.; Fernando, C. H. (Springer-Verlag, 1981)
An intensive and extensive sampling of the zooplankton from East and West Malaysia and Singapore yielded 63 cladoceran species of which 26 are recorded for this region for the first time. Redescriptions of a few species are given together with remarks on some others. The records include the first known occurrence of Alonella nana, Chydorus faviformis and Streblocercus pygmaeus in the tropics. The most diverse fauna was found in rice fields and ponds. The species composition is typical for a tropical region and lacks the families Polyphemidae, Leptodoridae and Holopedidae. Also Daphnia was extremely rare.